2019
DOI: 10.1038/s41598-019-52642-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal gastrin releasing peptide receptor expressing interneurons are controlled by local phasic and tonic inhibition

Abstract: Dorsal horn gastrin-releasing peptide receptor (GRPR) neurons have a central role in itch transmission. Itch signaling has been suggested to be controlled by an inhibitory network in the spinal dorsal horn, as increased scratching behavior can be induced by pharmacological disinhibition or ablation of inhibitory interneurons, but the direct influence of the inhibitory tone on the GRPR neurons in the itch pathway have not been explored. Here we have investigated spinal GRPR neurons through in vitro and bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…To determine the appropriate Cre driver for the genetically encoded Ca 2+ indicator GCaMP6s, we performed dual FISH studies. These showed extensive colocalization of the glutamatergic neuronal marker Vglut2 with Tacr1 (99.0% ± 0.6 of Tacr1 neurons) and Grpr (98.5% ± 0.5 of Grpr neurons) in SDH neurons, indicating that these are excitatory neuron populations (Figure 5c-e), in agreement with previous studies [20,25,71]. Therefore, we selectively targeted Vglut2-positive excitatory neurons within the SDH in Ca 2+ imaging experiments.…”
Section: Nk1r Is Expressed In Grpr Interneurons Within the Superficiasupporting
confidence: 89%
“…To determine the appropriate Cre driver for the genetically encoded Ca 2+ indicator GCaMP6s, we performed dual FISH studies. These showed extensive colocalization of the glutamatergic neuronal marker Vglut2 with Tacr1 (99.0% ± 0.6 of Tacr1 neurons) and Grpr (98.5% ± 0.5 of Grpr neurons) in SDH neurons, indicating that these are excitatory neuron populations (Figure 5c-e), in agreement with previous studies [20,25,71]. Therefore, we selectively targeted Vglut2-positive excitatory neurons within the SDH in Ca 2+ imaging experiments.…”
Section: Nk1r Is Expressed In Grpr Interneurons Within the Superficiasupporting
confidence: 89%
“…15 As suggested that GRP is released from glutamatergic interneurons in the SDH, different groups of researchers suggested that activation of GRPR + neurons through α-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid receptor (AMPAR) by glutamate is a key component of itch processing in the SDH. [33][34][35] We also recently demonstrated that GRP and glutamate cooperatively activate itch-responsive GRPR + neurons in the SDH under acute and chronic itching conditions. 15 Notably, i.d.…”
Section: Discussionmentioning
confidence: 88%
“…Secondly, GABA/glycine are adequate for regulating Tac2 / Ucn3 tdTom neurons through feedforward inhibition via GABAergic/glycinergic neurons 26 . Because mechanical itch travels through GRPR neurons, which are directly subject to GABA/glycine-mediated inhibition of galanin neurons 54 , 56 , 57 , the physiological relevance of inhibitory regulation of Tac2 / Ucn3 tdTom neurons is currently unclear. It is possible that Tac2 / Ucn3 tdTom neurons are kept in a quiescent state under an inhibitory control, which may explain why mechanical itch is rather infrequently experienced.…”
Section: Discussionmentioning
confidence: 99%